Real diagnoses and nursing intervention proposals for multiple trauma victims - Kátia Cilene Godinho Bertoncello; Cibele D'Avila Kramer Cavalcanti; Patricia Ilha (Universidade Federal de Goias, 2013)
This descriptive quantitative study was performed at a reference trauma hospital emergency room with the objective to identify the nursing diagnoses presented by multiple trauma victims treated between February and April of 2012 and, next, propose nursing interventions. Evaluations were conducted with 41 patients referred by pre-hospital care services. All patients were 18 years of age or older, male and female, not pregnant and using the NANDA International Taxonomy II and Nursing Interventions Classification. Among the 25 identified diagnoses, the most prevalent were: acute pain; impaired physical mobility; impaired walking; bathing self-care deficit; dressing self-care deficit; intimate hygiene self-care deficit; impaired bed mobility; impaired transfer ability; impaired skin integrity; impaired tissue integrity; feeding self-care deficit; and ineffective respiratory pattern. Nest, 82 nursing interventions were proposed aiming to reduce patient harm. Descriptors: Multiple Trauma; Nursing Diagnosis; Emergency Nursing.